Diabetic foot disease: impact of ulcer location on ulcer healing. Issue 5 (5th July 2013) - Pickwell, Kristy M.; Siersma, Volkert D.; Kars, Marleen; Holstein, Per E.; Schaper, Nicolaas C.; ,
Abstract Background Healing of heel ulcers in patients with diabetes is considered to be poor, but there is relatively little information on the influence of ulcer location on ulcer healing. Methods The influence of ulcer location on time to healing of diabetic foot ulcers was analysed by multivariate Cox regression analysis for 1000 patients included in the Eurodiale study, a prospective cohort study of patients with diabetic foot disease. Results Median time to healing was 147 days for toe ulcers [(95% confidence interval (CI) 135–159 days)], 188 days for midfoot ulcers (95% CI 158–218 days) and 237 days for heel ulcers (95% CI 205–269 days) (p < 0.01). The median time to healing for plantar ulcers was 172 days (95% CI 157–187 days) and 155 days (95% CI 138–172 days) for nonplantar ulcers (p = 0.71). In multivariate Cox regression analysis, the hazard ratio for ulcer healing for midfoot and heel ulcers compared with toe ulcers was 0.77 (95% CI 0.64–0.92) and 0.62 (95% CI 0.47–0.83), respectively; the hazard ratio for ulcer healing for plantar versus nonplantar ulcers was 1 (95% CI 0.84–1.19). Other factors significantly influencing time to healing were the duration of diabetes, ulcer duration, the presence of heart failure and the presence of peripheral arterial disease. Conclusions Time to ulcer healing increased progressively from toe to midfoot to heel, but did not differ between plantar and nonplantar ulcers. Our data also indicate that risk factors for longer time to healing differ from factors that affect the ultimate number of ulcers that heal (healing rate). Copyright © 2013 John Wiley & Sons, Ltd.